International business strategy : rethinking the foundations of global corporate success - Verbeke, Alain, (Cambridge University Press, 2013)
Verbeke provides a new perspective on international business strategy by combining analytical rigour and true managerial insight on the functioning of large multinational enterprises (MNEs). With unique commentary on 48 seminal articles published in the Harvard Business Review, the Sloan Management Review and the California Management Review over the past three decades, Verbeke shows how these can be applied to real businesses engaged in international expansion programmes, especially as they venture into high-distance markets. The second edition has been thoroughly updated and features greater coverage of emerging markets with a new chapter and seven new cases. Suited for advanced undergraduates and graduate courses, students will benefit from updated case studies and improved learning features, including 'management takeaways', key lessons that can be applied to MNEs and a wide range of online resources.